Impacts of Information and Communication Technology on Libraries in Ghana: A review - Markwei, E.D.; Bilson, A.P.K.E. (Library Philosophy and Practice, 2019)
The purpose of this article was to provide a review of literature on the impacts of Information and Communication Technology (ICT) on Libraries in Ghana. Some of the ICT impacts identified were in the area of cataloguing and classification, online public access catalogue, acquisitions, video conferencing, web 2.0 and social media tools, online searching and retrieval, electronic resources, digitization, electronic/digital libraries and institutional repositories, library website, indexing and abstracting, technical services, bibliographic instruction/library instruction, mobile digital library, interlibrary loan and document delivery, information access and video and photo libraries. Our review indicates that despite the tremendous changes brought about by ICT to Ghanaian libraries, they are still faced with a lot of challenges that needs to be addressed to enable these libraries to operate efficiently to provide the required information resources to its users. It also proposes recommendations for policy makers especially management of institutions with libraries, practitioners especially Librarians, researchers, students and all others who have an interest in library activities. Some of these recommendations include the provision of funding for ICT equipment and infrastructure, maintenance and updating of ICT equipment, training of users and staff, involvement of Management in ICT related issues in libraries, provision of uninterrupted power supply supplemented with standby generators and the provision of fast and uninterrupted bandwidth.
Research Article
Keywords: Information and Communication Technology; Libraries; Ghana; indexing and abstracting